The effects of building‐related factors on classroom relative humidity among North Carolina schools participating in the 'Free to Breathe, Free to Teach' study. (3rd January 2015) - Angelon‐Gaetz, K. A.; Richardson, D. B.; Lipton, D. M.; Marshall, S. W.; Lamb, B.; LoFrese, T.
Abstract: Both high and low indoor relative humidity (RH) directly impact Indoor Air Quality (IAQ), an important school health concern. Prior school studies reported a high prevalence of mold, roaches, and water damage; however, few examined associations between modifiable classroom factors and RH, a quantitative indicator of dampness. We recorded RH longitudinally in 134 North Carolina classrooms ( n  = 9066 classroom‐days) to quantify the relationships between modifiable classroom factors and average daily RH below, within, or above levels recommended to improve school IAQ (30–50% or 30–60% RH). The odds of having high RH (>60%) were 5.8 [95% Confidence Interval (CI): 2.9, 11.3] times higher in classrooms with annual compared to quarterly heating, ventilating, and air‐conditioning (HVAC) system maintenance and 2.5 (95% CI: 1.5, 4.2) times higher in classrooms with HVAC economizers compared to those without economizers. Classrooms with direct‐expansion split systems compared to chilled water systems had 2.7 (95% CI: 1.7, 4.4) times higher odds of low RH (<30%). When unoccupied, classrooms with thermostat setbacks had 3.7 (95% CI: 1.7, 8.3) times the odds of high RH (>60%) of those without setbacks. This research suggests actionable decision points for school design and maintenance to prevent high or low classroom RH.